White Fulani (Bunagi) of Nigeria - Ngere, L.O. (Food and Agriculture Organization of the United Nations, 1985)
Paper presented at the expert committee meeting on animal genetic resources in Africa, 1983. Reviews the White Fulani (Bunaji) in Nigeria. Describes the breed composition of the national herd, natural habitat and systems of husbandry. Detailed discussions on breed characteristics, constraints on productivity, disease and future prospects included.